Chapter Edición crítica, problemas textuales y de autoría: métrica y ortología en Lope de Vega - Fernández Rodríguez, Daniel (Studi e saggi, 2021)
Through examples taken from comedies recently attributed to Lope de Vega, this article deals with certain problems that should be considered when studying or editing plays of doubtful authorship. The analysis focuses on methods traditionally used to resolve problematic attributions, such as the study of versification, orthoepy and syllable counting. The conclusion argues that all of these tools -as well as the landmark works by Morley and Bruerton or W. Poesse - still offer great surprises and challenges for researchers. Thus, the development of new methods, such as stylometry, should not impel us to dismiss the classic approaches. Quite the opposite: old and new methods inform one another.